2021
DOI: 10.1590/2447-536x.v27i1.2230
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of browning problem during the callogenesis of Spartium junceum L.

Abstract: During different phases of in vitro culture, plant tissues may be exposed to some stresses that never encounter in their natural habitats. The most significant stresses which interfere with in vitro culture are pathogenic contamination and browning disorder. Since browning sign is occurred during all phases of in vitro culture of Spartium junceum L., the present study was done preventing explants from browning during disinfection and callogenesis phases using exposure time of sterilants (ethanol 0, 30, 60 s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Some studies have shown that the application of PVP in a culture medium cause elimination of phenolic compounds and reduces the browning of explants 67 , 68 . Because PVP can adsorb polyphenols, it can be argued that PVP, as a polyphenol absorbing agent, is effective in reducing vascular occlusion and has positive synergistic effects with MWCNTs in improving water uptake by the stem.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the application of PVP in a culture medium cause elimination of phenolic compounds and reduces the browning of explants 67 , 68 . Because PVP can adsorb polyphenols, it can be argued that PVP, as a polyphenol absorbing agent, is effective in reducing vascular occlusion and has positive synergistic effects with MWCNTs in improving water uptake by the stem.…”
Section: Discussionmentioning
confidence: 99%
“…Ndakidemi et al (2014) reported that incorporation of 200-250 mg/litre of ascorbic acid into the medium significantly controlled lethal browning in nodal culture of Brahylaena huillensis. Supplementation of 0.5% PVP into culture medium prevented explants browning in callus culture of nodal explant of Spartium junceum L. (Taghizadeh and Dastjerd, 2021).…”
Section: Incorporation Of Antioxidants Into Mediummentioning
confidence: 94%
“…The redness of color could be caused by the long period of culture and the redness color could cause the dead of callus [8]. To overcome this problem, the media need to add PolyvinylPyrrolidone (PVP) in future research [9]. In table 4 above showed that 2,4D0.5 Pic2 media gave callus the best result of callus proliferation of Sumenep variety.…”
Section: Callus Proliferationmentioning
confidence: 99%